Acid-base disorders : clinical evaluation and management - Reddi, Alluru S. (Switzerland : Springer, 2020)
This book provides a concise yet comprehensive overview of acid-base disorders. Each chapter reviews an acid-base disorder, covering pathophysiology, evaluation, and management of the disorder. The chapters also include clinical cases and a Q&A section, based on scenarios and questions that clinicians regularly encounter when treating patients with these disorders. The book concludes with two chapters on acid-based disorders in special patient populations, including critically ill patients, pregnant patients, and surgical patients.
Keywords: DESEQUILIBRIO ACIDO-BASE; DESEQUILIBRIO ÁCIDO-BASE -- TRATAMIENTO; DESEQUILIBRIO ÁCIDO-BASE -- DIAGNÓSTICO